Philanthropy and ERM: The Dance of Innovation. Issue 2 (3rd April 2019) - England, Lenore
Abstract: The author details establishing a type of philanthropic enterprise that applies the innovative work processes she employed as an electronic resources librarian at an academic library and within a library consortium. Approaches to this philanthropic work, especially through the strategic application of innovation and business process management are described, as well as a vision to support library organizations and electronic resources management through innovative philanthropy. Her work in establishing a new Philanthropy Advisory Group for the American Library Association provides an example of this philanthropic approach.